In The Blood: Connecting Variant to Function In Human Hematopoiesis. Issue 8 (August 2020) - Nandakumar, Satish K.; Liao, Xiaotian; Sankaran, Vijay G.
Abstract : Genome-wide association studies (GWAS) have identified thousands of genetic variants associated with a range of human diseases and traits. However, understanding the mechanisms by which these genetic variants have an impact on associated diseases and traits, often referred to as the variant-to-function (V2F) problem, remains a significant hurdle. Solving the V2F challenge requires us to identify causative genetic variants, relevant cell types/states, target genes, and mechanisms by which variants can cause diseases or alter phenotypic traits. We discuss emerging functional approaches that are being applied to tackle the V2F problem for blood cell traits, illuminating how human genetic variation can impact on key mechanisms in hematopoiesis, as well as highlighting future prospects for this nascent field. Highlights: V2F studies aim to decipher the mechanisms by which GWAS-nominated genetic variants contribute to specific phenotypes. Targeted V2F studies in blood cell traits have led to novel insights into hematopoiesis in areas including hemoglobin switching, the production of mature blood cells, and immune regulation. Scalable perturbation methods are enabling global V2F studies by prioritizing variants and target genes for further experimental studies to validate the associated phenotype. Future V2F studies might help to elucidate how common genetic variants influence rare blood disorders, the risk of acquiring blood cancers, and other cryptic hematopoietic phenotypes.